Development of physical culture among the school youth of Donbass (20-ies of XX century) - Galchenko A.N (Kharkov National Pedagogical University, 2010)
The politics of the Soviet authority in business of introduction physical training in an education system is shined. The condition of process of physical development is considered within the limits of school educational institutions. The place of physical training in structure of the general education of youth is found out. Diffculties of an initial stage are analyzed. Shift and dynamics of process are traced. It is marked, that already at the end of frst half of 1920 to process of physical development the most part of schools of Donbass has joined.